First record and a new taxon of Stammericaris Jakobi, 1972 (Copepoda, Harpacticoida) from the Philippines; with an amendment to the generic diagnosis and reassignment of three Palearctic species - Cottarelli, Vezio; Bruno, Maria Cristina (Zootaxa, 2025)
We report on the finding of Stammericaris galichai sp. nov. in the hyporheic habitat of Cantingas River, Sibuyan Island, the Philippines. The new species is attributed to the genus based on the morphology of the male antennule (of the “pocket-knife” type); the presence of a hook on the inner margin of the basis of the male first pereopod; the male third pereopod with a long apophysis and two groups of outer spinules on the first exopodal segment; the endopodite of the male forth pereopod reduced, but corresponding to the basic morphology of the genus, and the basis ornamented with two spinules on inner margin, one of which long and inwardly-curved, one small and with apex consisting of three small lobes. Stammericaris galichai sp. nov. does not have one taxonomically and morphologically closest species within the genus, possibly due to its geographical isolation. Based on some aspects of the morphology of Stammericaris galichai sp. nov. (namely, the shape of the fifth pereopod) and other species of Stammericaris, the description of the genus is slightly amended, and the Palearctic taxa Parastenocaris balcanica Petkovski, 1959, P. nertensis Rouch, 1990, P. triphyda Cottarelli & Bruno, 1993 are transferred to the genus Stammericaris. Stammericaris galichai sp. nov. is the first representative of the genus for the Philippines, and for the entire Oriental Region. The faunistic and biogeographical relevance of the new species is discussed with particular focus on the discovery of this freshwater stygobitic species in a volcanic island which has never been in contact with other landmasses. A map of the distribution of Parastenocarididae hitherto known for the Philippines, including a new station in Mindoro for the endemic Parastenocaris distincta Cottarelli, Bruno & Berera, 2006, is also provided.